A SURVEY ON OPTIMAL IPV4 TO IPV6 TRANSITION TECHNIQUES - Sivaprakash, Aparna; Kayalvizhi, S. (International Journal of Research -GRANTHAALAYAH, 2016)
The number of global internet users has been growing exponentially, thereby requiring a much larger number of unique IP addresses for all the connected networking devices. The prevalent IP version 4 is not able to meet the current requirement for IP addresses and to meet the future IP address requirement, a new version IPv6 has been introduced since 1999. However IPv6 is not backward compatible with IPv4.since it is not possible to migrate all the networking devices to IPv6 in a single day, IPv4 and IPv6 are going to be used in parallel for some time. Here we aim to provide a Literature Survey which showcases the various different techniques to implement IPv4 to IPv6 transition and figure out the most optimal method to increase the network performance.